Knowledge of cataracts and eye care utilization among adults aged 50 and above in rural Western China - Du, Kang; Guan, Hongyu; Zhang, Yunyun; Ding, Yuxiu; Wang, Decai (Frontiers in Public Health, 2022)
Background: Cataracts are highly prevalent in rural China, but patient utilization of eye care services is low. Cataract knowledge is regarded as an important factor in eye care utilization. Few studies, however, have been conducted to measure the level of cataract knowledge and its relationship with eye care utilization among older adults in rural China. Hence, we described cataract knowledge and investigated the relationships between cataract knowledge and eye care utilization among adults (≥50 years) in rural western China. Methods: A large community-based cross-sectional study was conducted from October to December 2020 among adults aged 50 years and older in 73 rural villages in Qingcheng County, Western China. The participants underwent an eye examination at their village clinic to determine whether they had cataracts. Participants also answered a questionnaire about cataracts, eye care utilization status, and sociodemographic characteristics. The collected data underwent descriptive and multiple logistic regression analyses. Results: The eye examinations revealed that 45.15% (675/1,495) of participants had cataracts in at least one eye, yet 90.67% (612/675) were left untreated. The average score achieved by participants about cataract knowledge was 4.91 points (total score was 8 points). Correct knowledge about cataracts was positively associated with cataract screening and cataract surgery. Elders with better cataract knowledge were 2.21 times more likely to undergo cataract screening (OR, 2.21; 95%CI, 1.54-3.16) and 5.61 times more likely to undergo cataract surgery (OR, 5.61; 95%CI, 2.87-10.98). More than half had three fundamental misconceptions about how cataracts should be treated, how much they should cost, and when they should be treated. Participants who did not have these misconceptions were more likely to receive cataract screening by 1.21-2.02 times and cataract surgery by 1-76-3.48 times. Conclusion: There are misunderstandings about cataract treatment methods, treatment costs and timing in the sample areas. A better understanding of cataracts was significantly positively associated with cataract screening and cataract surgery. Health education on cataracts and regular eye examinations are needed to improve eye care utilization in rural China.